Cultural studies 50 years on history, practice and politics - Connell, Kieran; Hilton, Matthew (Rowman & Littlefield International, 2016)
"Cultural Studies 50 Years On explores how the political, social and cultural contexts of the early 21st century influenced the object and method of doing cultural studies. In bringing together a historical reassessment of the Centre with present-day questions regarding the future of the field the aim is not to reduce cultural studies to the work of a single, now-defunct institution. Instead it aims to utilize what is a critical moment in the trajectory of the field in order to take stock of where it has come from and to explore where it might be going."--Provided by publisher.